2017
DOI: 10.4049/jimmunol.1700717
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Neutrophils with Macrophages Promotes IL-1β Maturation and Contributes to Hepatic Ischemia–Reperfusion Injury

Abstract: Accumulating evidence suggests that IL-1β plays a pivotal role in the pathophysiology of hepatic ischemia-reperfusion (I/R) injury; however, the mechanism by which I/R triggers IL-1β production in the liver remains unclear. Recent data have shown that neutrophils contribute to hepatic I/R injury independently of the inflammasomes regulating IL-1β maturation. Thus, we investigated the role of neutrophils in IL-1β maturation and tissue injury in a murine model of hepatic I/R. IL-1β was released from the I/R live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 24 publications
3
33
1
1
Order By: Relevance
“…Previous investigations have demonstrated that inflammation contributes to the development of hepatic I/R injury; therefore, we performed real‐time RT‐PCR analysis to assess the expression of inflammatory cytokines and cell markers. The expression of Il1b , Il6 , Tnfa , Ccl2 , and Ly6g (neutrophil marker) was increased in the I/R liver, and this increase was significantly inhibited by Fer‐1 (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations have demonstrated that inflammation contributes to the development of hepatic I/R injury; therefore, we performed real‐time RT‐PCR analysis to assess the expression of inflammatory cytokines and cell markers. The expression of Il1b , Il6 , Tnfa , Ccl2 , and Ly6g (neutrophil marker) was increased in the I/R liver, and this increase was significantly inhibited by Fer‐1 (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Overnight (16 hours)‐fasted mice underwent hepatic I/R or sham operation. Partial hepatic ischemia was produced as previously described with some modifications . Briefly, mice were anesthetized with isoflurane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histology and immunohistochemistry were performed as described previously 16 . Paraffin-embedded tissue sections were stained with hematoxylin and eosin.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Previous studies have shown that circulating IL-1b, TNF-a, and CRP are significantly elevated early after hemorrhagic shock, hypoxia, and ischemia-reperfusion injury. [30][31][32] Elevations of circulating IL-6 occur early and have been shown to correlate with severe trauma and degree of tissue injury. 33 In addition, our analysis revealed 45 bone marrow miRs with significantly altered expression after LCHS/CS compared with those rodents that received propranolol after LCHS/CS and naïve rodents.…”
Section: Discussionmentioning
confidence: 99%